2018
DOI: 10.3390/ijerph15061095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cardiac Rehabilitation on Quality of Life, Depression and Anxiety in Asian Patients

Abstract: This study explored the effect of cardiac rehabilitation on quality of life, depression, and anxiety in Asian patients in Singapore. Out of the 194 patients who were recruited into the study, 139 patients (71.6%) completed both the pre- and post-cardiac rehabilitation questionnaires. Their ages ranged from 28 to 80 (M = 56.66, SD = 8.88), and 103 patients (74.1%) were males and 21 patients (15.1%) were females. As hypothesized, there was a statistically significant difference between the pre- and post-cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 39 publications
2
36
0
3
Order By: Relevance
“…The greater psychological burden found in our outpatient group may represent poor emotional coping and distress in response to having to manage their illness and be related to the low attendance of the outpatient chronic disease management program offered by the hospital. Similar challenges with rehabilitation program attendance have been described elsewhere and point out the importance of considering mental health and psychological distress as an explanation for early dropout, given their effectiveness in improving overall well-being among patients [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The greater psychological burden found in our outpatient group may represent poor emotional coping and distress in response to having to manage their illness and be related to the low attendance of the outpatient chronic disease management program offered by the hospital. Similar challenges with rehabilitation program attendance have been described elsewhere and point out the importance of considering mental health and psychological distress as an explanation for early dropout, given their effectiveness in improving overall well-being among patients [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 80%
“…In the absence of this work, HRQOL studies will play an important role as researchers attempt to describe the morbidity and suffering associated with cardiovascular disease in Vietnam. Generating a better understanding of this burden may be crucial when developing effective CVD rehabilitation programs, which have had demonstrable impacts on improving the HRQOL of patients in both Singapore [ 20 ] and Malaysia [ 21 ]. While previous reports have described the relationship between the development of CVD/ CVD risk factors and sociodemographic factors, what is less clear is how the HRQOL impacts of CVD are related to or determined by these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study did not investigate the effect of physical activity on psychological conditions such as depression, which can lead to work-related disability and productivity loss [ 52 ]. In fact, physical activity can reduce the severity of depression as well as improving cardiac function [ 53 ]. The present study only focused on anthropometric and biochemical indicators, but the psychological aspect could certainly be investigated in a future study on HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, psychological intervention is required to address this competition of control as it may affect adherence to treatment. Previous research found that cardiac patients who had poor adherence to cardiac rehabilitation reported lower levels of physical and mental quality of life and higher levels of depression post-cardiac rehabilitation [41].…”
Section: Discussionmentioning
confidence: 96%